2nd Edition of Health Emergency and Disaster Risk Management (Health-EDRM) - Chan, Emily Ying Yang; Lam, Holly Ching Yu; Chan, Emily Ying Yang; Lam, Holly Ching Yu (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Disasters such as earthquakes, cyclones, floods, heat waves, nuclear accidents, and large-scale pollution incidents take lives and incur major health problems. The majority of large-scale disasters affect the most vulnerable populations, which often comprise extreme ages, remote living areas, and endemic poverty, as well as people with low literacy. Health emergency and disaster risk management (Health-EDRM) refers to the systematic analysis and management of health risks surrounding emergencies and disasters, and plays an important role in reducing the hazards and vulnerability along with extending preparedness, responses, and recovery measures. This concept encompasses risk analyses and interventions, such as accessible early warning systems, the timely deployment of relief workers, and the provision of suitable drugs and medical equipment to decrease the impact of disasters on people before, during, and after an event (or events). Currently, there is a major gap in the scientific literature regarding Health-EDRM to facilitate major global policies and initiatives for disaster risk reduction worldwide.
English
Keywords: Public health & preventive medicine; infection spread and control; infection risk; human behavior; close contact; sensor-based; indoor environment; indoor positioning; head and body motion; open-plan office; disaster; psychosocial impacts; community resilience; Kumamoto earthquake; DMHISS; disaster psychiatry; Japan; acute mental health needs; duration of activity; DPAT (Disaster Psychiatric Assistance Team); cold; personal health protective behaviour; associated factors; risk perception; subtropical city; disaster responders; support; psychosocial; risk management; COVID-19; urban; health risks; Health-Emergency and Disaster Risk Management; biological hazard; pandemic; PHEIC; Hong Kong; Fukushima nuclear accident; mass media; Internet; public health practice; community mental health services; typhoon; hurricane; cyclone; strong wind levels; natural disaster; Health-EDRM; risk-taking behaviour; sensation seeking; landslide displacement; predictive uncertainty; ensemble prediction; probability combination scheme; quantile regression neural networks (QRNNs); kernel density estimation (KDE); Daegu; sense of belonging; pride; mental health